A highly stretchable strain sensor based on a graphene/silver nanoparticle synergic conductive network and a sandwich structure. Issue 19 (14th April 2016) - Chen, Song; Wei, Yong; Yuan, Xue; Lin, Yong; Liu, Lan
Abstract : A highly stretchable strain sensor with a graphene/silver nanoparticle synergic conductive network and a sandwich structure was fabricated. Abstract : Strain sensors with superb stretchability are highly desirable for applications in wearable devices. Here we report a simple method via immersion-swelling followed by in situ reduction to fabricate a highly stretchable strain sensor with a graphene/AgNPs synergic conductive network and a sandwich structure ( i.e., one insulating layer sandwiched between two conductive layers). In the strain sensor, AgNPs were in situ formed without adding any other organic stabilizer, and graphene nanosheets acted as a conductive bridge between them, ensuring the wearable sensor excellent initial electrical conductivity ( σ ≈ 1.4 × 10 5 S m −1 ). During stretching, the pure graphene/TPU insulating layer of the sandwich structure maintained the high stretchability, and the graphene located between the cracks of AgNPs resulted in the connection of conductivity networks under high strain (1000% maximum strain). What is more, the low detection limit (0.5%), high gauge factor (7 at 50% strain, 476 at 500% strain) and high working stability (more than 1000 cycles at 50% strain) of the strain sensor enable it to meet the needs for numerous applications in wearable devices.